DAMPAK LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN ENERGY YANG TERDAFTAR DI BEI DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERVENING - Dwipa, Bram Mahara; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2023)
Energy companies is a company that operates in the electric power sector for the benefit of society and the state. The company has an obligation to fulfill or pay off short-term and long-term financial obligations so that the company is said to be liquid. The aim of this research is to determine the significance of the influence of Liquidity and Profitability on Company Value through Share Prices. This research uses descriptive and quantitative research. The population in this research is 80 energy sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sampling technique in this research used the Purposive Sampling technique. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Liquidity has a negative but significant effect on Share Prices, Profitability has a negative but not significant effect on Share Prices, Liquidity has a significant positive effect on Company Value, Profitability has a positive but not significant effect on Company Value, Stock prices have a negative but not significant effect on firm value. The results of the indirect influence hypothesis test show that the Liquidity variable has a positive but not significant effect on Company Value through Share Prices, Profitability on Company Value through Share Prices has a positive but not significant effect.